PEMBERDAYAAN KADER PKK KELURAHAN ARGASUNYA MELALUI PEMBUATAN TEH DAUN KELOR SEBAGAI UPAYA PENCEGAHAN STUNTING - Sri Ayu Kurnia; Seilefa Putri Nabila; Fika Nurul Hidayah; Fatimah Fatimah (LPPM Universitas Nusa Mandiri, 2026)
Stunting remains a chronic nutritional problem in Indonesia and is closely linked to poor nutritional intake during the first 1,000 days of life, including breast milk production and feeding. In Argasunya Village, moringa plants are abundant but have not yet been optimally utilized as a lactation-supporting product. The purpose of this community service is to develop the capacity of PKK cadres in utilizing Moringa leaves by processing them into herbal tea, so that it can become an alternative to support increased breast milk production, while also encouraging economic empowerment based on local potential. Activities were conducted through outreach, training, hands-on practice, mentoring, and evaluation, involving 35 PKK cadres. Data were collected via pre- and post-tests and observation sheets. The results showed a significant increase in knowledge: before the activity, only 14% of cadres were in the “good” category, whereas after the intervention, this increased to 74%, with no participants in the “poor” category. More than 85% of participants were also able to correctly practice the stages of moringa tea production, resulting in hygienic and marketable products. The mentoring strengthened the cadres’ ability to produce and market moringa tea as a household business opportunity. Overall, this program was effective in enhancing the capacity of PKK cadres, supporting the promotion of exclusive breastfeeding, utilizing local potential, and contributing to the prevention of stunting in the community.